استراتيجيات تخطيط تعليم النحو في البرامج غير الرسمية: دراسة حالة في برنامج الإيمان بسورابايا - Achmad Riyadi; Musta’in Musta’in (Darul Yasin Al Sys, 2026)
This study examines the challenges facing Arabic grammar instruction in non-formal educational environments, where it is often viewed as a difficult and rigid subject due to the dominance of traditional methods that focus on rote memorization of rules without linking them to linguistic context, resulting in weak understanding and low learner motivation. The study aims to analyze instructional planning strategies for teaching grammar in the Al-Iman Specialized Program in Surabaya City by focusing on how learning objectives are formulated, materials are selected, teaching methods are applied, instructional media are used, and the learning process is evaluated. The study adopted a qualitative method using a case study design, with data collected through classroom observation, semi-structured interviews, document analysis, and a questionnaire in order to develop a comprehensive understanding of instructional practices within the program. The results showed that the program is characterized by a flexible learning environment and a level-based system, with learning objectives focused on understanding texts and applying rules in their contexts. It was also found that instructional materials are adapted and organized progressively, and that teaching methods combine the inductive approach with traditional methods. The program also uses both traditional and digital instructional media, in addition to continuous and final assessment methods. The results further revealed clear integration among the components of instructional planning. The study concludes that the effectiveness of grammar instruction is closely related to the quality of instructional planning and the integration of its elements, and that combining traditional and modern methods contributes to improving learners’ understanding and reducing the difficulty they experience in grammar. The study emphasizes the need to develop instructional planning strategies in non-formal environments by enhancing interactive learning, expanding the use of technology, activating cooperative learning, and training teachers to design integrated instruction. It also recommends that future quantitative studies be conducted to measure the impact of these strategies on students’ achievement in grammar.